Pelestarian Bahasa Lokal Pada Awig-Awig di Desa Tenganan Dauh Tukad, Karangasem - Ni Wayan Kertiasih; A. A. Inten Mayuni; Ida Bagus Astika Pidada (Universitas Warmadewa, 2023)
Tenganan Dauh Tukad Village as one of the Old Villages in Bali has a unique cultural tradition. This maintained tradition is set forth in customary rules in the form of awig-awig. Many terms in the local language written in awig-awig are not easy to understand, especially for the younger generation. If this situation is allowed to continue, the community is worried that the traditions that are upheld will fade or even disappear. The community expects that their customs and culture can be preserved. For this purpose, community service is carried out which aims to create a community in the preservation of the local language contained in the Awig-awig of Tenganan Dauh Tukad Village. Service partners are Bendesa adat with the target of community leaders and the younger generation. Three issues that need attention are: 1) an inventory of local terms, 2) a description of their meaning, and 3) a conservation strategy. The implementation method is carried out by counseling, FGD, and assistance in preparing a pocket book on local terms in awig-awig. The results of the service include: documentation of local language terms and their meanings, as well as the preparation of a pocket book of terms found in awig-awig.